PKM PELATIHAN PENGGUNAAN PERANGKAT PEMBELAJARAN DARING BAGI GURU-GURU DI SD KATOLIK STA. CLARA TOMOHON-SULAWESI UTARA - Theodorus Pangalila; Jan A Rattu (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Currently the whole world is experiencing problems in all aspects of life. This problem is caused by the outbreak of the corona virus or Covid-19 which is currently a global pandemic. Due to the Covid-19 outbreak, all aspects of life have changed, including the world of education. Currently the world is shaken by the Corona Virus or Covid-19 outbreak, and Indonesia is no exception. The Indonesian government has taken a number of policies to break the chain of transmission of Covid-19. Its main policy is to prioritize the health and safety of the people. Work, worship and study from home. UNESCO stated that the Covid-19 pandemic threatens 577,305,660 students from pre-primary to high school education and 86,034,287 students from higher education worldwide. Like the policies taken by various countries affected by the COVID-19 disease, Indonesia has closed all educational activities. At the primary, secondary and higher education levels, technically the distance learning process also encountered many obstacles. Students from families who do not have internet access or even do not have mobile phones will miss learning when learning assignments are delivered through WhatsApp or other applications. Responding to such conditions, the school should provide wisdom, for example by giving assignments in the form of working papers. Teachers are the backbone of education in schools, therefore teachers need to be prepared to face changes in learning practices from offline to online. The problems faced are: (1) Online learning due to the Covid-19 pandemic brings changes in learning models and approaches. (2) Many teachers do not understand and are skilled in using online learning tools such as: Google Classroom and. Edmodo. (3). Lack of socialization about how to use Google Classroom and. Edmodo for teachers. The solution offered in this activity is the use of Google Classroom and. Edmodo for teachers.